Robust non-fragile sampled-data control for offshore steel jacket platforms - Zhang, Bao-Lin; Meng, Mao-Mao; Han, Qing-Long; Zhang, Xian-Ming (Nonlinear dynamics, 2016)
This paper is concerned with the non-fragile sampled-data control problem for an offshore platform subject to parametric perturbations of the system and admissible gain variations of the controller. By purposefully introducing a time-varying time-delay into control channel, designing a sampled-data controller for the original system is transformed into synthesizing a state feedback controller for a time-varying time-delay system. A sufficient condition on the existence of a robust non-fragile sampled-data controller is derived. Then, a robust non-fragile sampled-data controller is designed and its effectiveness is investigated based on the simulation results. It is demonstrated that (1) the designed non-fragile sampled-data controller is capable of reducing the oscillation amplitudes of the floors of the offshore platform system significantly; and (2) compared with the robust sampled-data controller and the classical robust controller as well as the robust delayed controller, the oscillation amplitudes of the floors of the system under the three controllers are almost at the same level, while the control force required by the robust sampled-data controller is less than the one by the continuous-time controllers.